1988
DOI: 10.1177/002204268801800309
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Cocaine Use and Sexual Behavior

Abstract: The research discussed here explores the sexual behavior of two hundred and twenty-eight heavy users of cocaine. Intensive, face-to-face, tape-recorded interviews with each user uncovered some interesting differences in sexuality among various user groups. Far example, male users were found to have greater levels of sexual enhancement from cocaine, than were female users. Another finding was that freebasers and snorters of the drug had similar levels of sexual impairment, while injectors experienced far worse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
0
6
0
6
Order By: Relevance
“…Fifty-five respondents (25%) re¬ ported either giving or receiving sexual favors for drugs or money; boys (25%) were as likely as girls (24%) to report participation in drugs-sex-money ex- (20) (28-57) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) changes. As shown in Table 2, those who reported combining crack use with sexual relations were more likely to report engaging in such exchanges (40%) than those who did not (9% [P<<.0001]), and those who reported that they used crack daily were more likely to report engagement in such ex¬ changes (43%) than nondaily users (20% [P<.01]).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-five respondents (25%) re¬ ported either giving or receiving sexual favors for drugs or money; boys (25%) were as likely as girls (24%) to report participation in drugs-sex-money ex- (20) (28-57) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) changes. As shown in Table 2, those who reported combining crack use with sexual relations were more likely to report engaging in such exchanges (40%) than those who did not (9% [P<<.0001]), and those who reported that they used crack daily were more likely to report engagement in such ex¬ changes (43%) than nondaily users (20% [P<.01]).…”
Section: Resultsmentioning
confidence: 99%
“…66 MacDonald et al found that of men who had used cocaine for 1 year or longer, 66% reported to have erection difficulties. 67 With chronic abuse of cocaine, sexual dysfunction is attributed mainly to hyperprolactinemia and downregulation of the hypothalamic dopaminergic receptors. 68 There are reports of cases of priapism associated with intracavernosal injection of cocaine.…”
Section: ) Cocainementioning
confidence: 99%
“…Aunque las evidencias de que el consumo crónico de sustancias afecta al comportamiento sexual (Peugh y Belenko, 2001) y al deseo sexual en los consumidores de cocaína (Cocores, Miller, Optas y Gold, 1988;MacDonald, Waldorf, Reinarman, y Murphy, 1988;Henderson, Boyd y Whitmarsh, 1995;Wetherby, Shultz y Chitwood, 1992) y de alcohol (Crenshaw y Goldberg, 1996;Rosen, 1991), el estudio de la respuesta emocional de adictos a drogas ante estímulos incondicionados como los sexuales es escaso. Este hecho dificulta la elaboración de hipótesis basadas en investigaciones previas y nos obliga a hipotetizar basán-donos en la evidencia clínica de la falta de interés, manifestada con frecuencia por los adictos a drogas en tratamiento, hacia los eventos afectivos cotidianos, entre los que cabe mencionar los sexuales.…”
Section: Introductionunclassified